PROFESSOR EMERITUS OF THE KYIV UNIVERSITY, TOLSTOY MYKHAYLO – GEOLOGIST-GEOPHYSICIST - Шабатура, О. (Київський національний університет імені Тараса Шевченка, 2017)
The article describes the scientific, pedagogical and management activities of the prominent Ukrainian scientist, organizer of the scientific structure of the Kiev University, the famous geologist-geophysicist – Professor Emeritus Tolstoy Mykhailo. The evolution from the scientistpragmatist to the founder of the interbranch scientific school is covered. There are the stages of foundation, development and solving of a number of fundamental problems of geology: the quantitative analysis of the distribution of chemical elements and physical properties of magmatic formations using mathematical methods, paleogeodynamic and metallogenic prediction based on the analysis of complex data, geophysics of landscapes; numerous heritage of applied developments – an unique databases of geological data of intrusive and volcanogenic rocks, lithotheque, a fund of standards, the monitoring sites etc.

Описано наукову, педагогічну та організаційну діяльність видатного українського науковця, організатора наукової структури Київського університету, відомого геолога-геофізика, заслуженого професора М. І. Толстого. Висвітлюється його еволюція від ученого-прагматика до засновника наукової школи між вищими навчальними закладами, з етапами постановки, розробки і вирішення низки фундаментальних завдань геології: кількісний аналіз розподілу хімічних елементів і фізичних властивостей магматичних утворень з використанням математичних методів, палеогеодинамічне і металогенічне прогнозування на основі аналізу комплексних даних, геофізики ландшафтів тощо. Численна і його спадщина прикладних розробок – створено унікальні бази геологічних даних інтрузивних і вулканогенних порід, літотека, фонд стандартів складу, полігони і вимірювальні моніторингові майданчики тощо.
ЗАСЛУЖЕНИЙ ПРОФЕСОР КИЇВСЬКОГО УНІВЕРСИТЕТУ ТОЛСТОЙ МИХАЙЛО ІВАНОВИЧ – ГЕОЛОГ-ГЕОФІЗИК